Evaluation of corneal topography, pachymetry and higher order aberrations for detecting subclinical keratoconus. (11th February 2022) - Kandel, Sandeep; Chaudhary, Meenu; Mishra, Sanjeeb K; Joshi, Niraj D; Subedi, Manish; Puri, Prajjol R; Gyawali, Parash; Bist, Jeewanand; Kandel, Himal
Abstract: Purpose: To compare corneal topography, pachymetry and higher order aberrations in keratoconic and normal eyes; to investigate their association in keratoconic eyes; and to determine their diagnostic ability for detecting subclinical keratoconus in a Nepalese population. Methods: Ninety‐six eyes of 48 keratoconus patients and 50 normal eyes of 50 control subjects were included in this study. The eyes of keratoconus patients were classified into four different study groups: subclinical, stage 1, stage 2 and advanced stage keratoconus. In each eye, corneal topography, pachymetry and corneal aberrometry indices were measured using a Sirius corneal tomographer. The study parameters of keratoconic eyes were compared with normal eyes, and the possible association of corneal aberrometry with topography and pachymetry indices was investigated. The area under curve (AUC) of receiver operating characteristic (ROC) curves along with optimal cutoff values with best sensitivity and specificity were also determined for each index to detect subclinical keratoconus. Results: All the indices except average keratometry measurements (Kavg and mmavg ) and spherical aberration (SA) were found to be significantly different in subclinical keratoconus compared to the control group ( p < 0.05). In keratoconic eyes, all corneal aberrations were significantly correlated with the topography and pachymetry indices (range of ρ : −0.25 to 0.96; all p < 0.05) except for trefoil and minimum corneal thickness (Thkmin ). All the indices except Kavg, mmavg and SA showed excellent diagnostic ability (AUC > 0.90) in detecting subclinical keratoconus. The cutoff values proposed for the asymmetry index of the corneal back surface (SIb ), Strehl ratio of point spread function (PSF), coma and Baiocchi‐Calossi‐Versaci index of corneal back surface (BCVb ) each showed excellent sensitivity (100%) and specificity (≥97%). Conclusions: Corneal higher order aberrations were found to be significantly elevated in subclinical keratoconus compared to healthy controls. SIb, PSF, coma and BCVb were identified as the most powerful Sirius indices for the detection of subclinical keratoconus.